The Role of - Bangu Bangu; Yuhanah Yuhanah; Grace Tedy Tulak; Heriviyatno Julika Siagian (Kesmas Indonesia, 2021)
Hypertension is currently still a health problem in both developed and developing countries because if it is not controlled, it will develop and cause complications. The role of the family is needed in controlling hypertension. Family has a role as caregiver in improving the health status of sick family members, because family is the main support for hypertensive patients in maintaining health. This study aims to describe the role of the family towards family members suffering from hypertension. This research is a qualitative research with a phenomenological approach. The technique of taking participants in this study used a nonprobability sampling technique, namely purposive sampling. There are 5 informants in this study. Data collected using unstructured interview techniques (unstructurer interview). The data validity test that was carried out included credibility test, transferability test, and confirmability test. Data analysis was performed using content analysis method. The results of this study are expected that the family can increase its role as a caregiver in providing care for family members who suffer from hypertension. The health status of people with hypertension is very much determined by how active the family is in providing care for their family members.